PENENTUAN TANGGAL BAU NYALE DALAM KALENDER ROWOT SASAK: (Analisis Sosial Adat Budaya) - Heri Zulhadi (Ulumuna: Jurnal Studi Keilsman, 2018)
The cultural custom is a complexity that is incorporated in a society which includes knowledge, beliefs, arts, morals, laws, customs, abilities and habits in humans within members of the community which in which a mutually agreed and implemented rule is formed. The calendar is a marker of time to identify historical events in human civilization (society) in carrying out everyday life and lasts for a certain period. Calendar is made as a reference for humanity in determining matters relating to worship, culture and even other important jobs. Related to the topic of discussion in this paper what is meant by the Sasak community is the regional tribe on the island of Lombok, West Nusa Tenggara. In the implementation of the Sasak traditional Bau Nyale is a celebration moment to commemorate the sacrifice of the princess's figure named Mandalika which transforms into a sea worm. The determination of the 20th in the Rowot Sasak Calendar was first held in consultation with traditional manners called Sangkep Warige, which was attended by traditional leaders and experts, in which the meeting was to look for characteristics and related natural phenomena in determining the date of implementation of the Nyale.